PERSPECTIVE ON PROTECTION OF THE RIGHTS OF MINORS IN MARRIAGE DISPENSATION IN RELIGIOUS COURTS - Yanuar Hakim Nst; T.Riza Zarzani; Andoko , Andoko (International Journal of Synergy in Law, Criminal, and Justice, 2025)
Child marriage is still a serious problem in Indonesia even though the minimum age for marriage has been raised through Law Number 16 of 2019. One of the legal loopholes that allows child marriage to continue to occur is the marriage dispensation mechanism that can be submitted to the Religious Court for urgent reasons. In practice, almost all requests for marriage dispensation are granted, with the main reasons being pregnancy outside of marriage and social pressure. This shows that increasing the minimum age for marriage has not been fully effective in preventing child marriage. This study uses a sociological legal approach with a qualitative descriptive method to analyze the legality of marriage dispensation for minors. The results of the study indicate that there is inconsistency in the application of marriage dispensation, where judges often grant requests without considering the child's physical, mental, and social readiness. In addition, there is a contradiction in the regulation, where the Child Protection Law requires parents to prevent child marriage, but on the other hand, the Marriage Law still provides an opportunity to apply for dispensation. From an Islamic legal perspective, child marriage should not only be viewed from a formal legal aspect, but also consider the maqashid sharia, namely protection of the soul, mind, and descendants. Therefore, stricter legal reform is needed in granting marriage dispensation, including strengthening regulations, supervision of religious court decisions, and increasing public awareness of the negative impacts of child marriage. Thus, marriage dispensation must really be used as a last resort (ultimum remedium) in emergency conditions and not as a means to legalize child marriage, so that the protection of children's rights can be realized optimally.